2018
DOI: 10.1017/jog.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Elevation change of Fedchenko Glacier, Pamir Mountains, from GNSS field measurements and TanDEM-X elevation models, with a focus on the upper glacier

Abstract: ABSTRACT. Fedchenko Glacier experienced a large thickness loss since the first scientific investigations in 1928. As the largest glacier in the Pamir Mountains, this glacier plays an important role for the regional glacier mass budget. We use a series of Global Navigation Satellite Systems observations from 2009 to 2016 and TanDEM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 31 publications
3
50
0
Order By: Relevance
“…Some geodetic mass-balance studies have therefore applied multi-meter corrections to account for radar penetration (e.g. Melkonian and others, 2014; Round and others, 2017; Lambrecht and others, 2018). However, over wet glacier surfaces radar penetration is limited to a few centimeters below the surface (Mätzler and Schanda, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Some geodetic mass-balance studies have therefore applied multi-meter corrections to account for radar penetration (e.g. Melkonian and others, 2014; Round and others, 2017; Lambrecht and others, 2018). However, over wet glacier surfaces radar penetration is limited to a few centimeters below the surface (Mätzler and Schanda, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…However, since additional X-band radar penetration was not considered, the penetration depth of the C-band radar we obtained was likely underestimated when calculating the elevation difference between TOPO DEM or TSX/TDX DEM and SRTM C-band DEM. Several studies have reported that the average penetration depth of the X-band radar could reach 2-4 m or less under dry-snow conditions over the accumulation region of glaciers in the Karakoram [25] and Western Pamir [61] mountain ranges. However, the precipitation in our study region is much less than that in the Karakoram and Western Pamir, especially during winter, and the thickness and extent of the dry snow might be much less than in the Karakoram and Western Pamir.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…The application of TanDEM-X data introduces a bias caused by the penetration of the radar signal into snow. However, the magnitude of this effect depends strongly on snow and firn conditions and, hence, can vary considerably (Lambrecht et al, 2018).…”
Section: Uncertainties and Biasmentioning
confidence: 99%